Telling Livelihood Hi(stories) of the Dom Community: A Resilience Perspective - Magar , Bishnu (New Journey, 2025)
This study applied qualitative approach with narrative inquiry as a methodological road map. It helped me to explore the livelihood strategies of Dom community who are minority and highly marginalized ethnic group of people in Urlabari Municipality. The livelihood life hi(stories) and lived experiences are represented by vignettes which are used as lively analytical tools. The Dom community who falls at the edge of social, economic, political and environmental development facets that have caused critical survival to struggle due to the advent of the liberal market system in the country. The survival vulnerabilities induced by the loss of their traditional and indigenous knowledge and skills as a means of livelihood have put them in the vicious circle of poverty for generations. The circumstances of livelihood shocks which they faced put them in the absolute transition in their livelihood practice from traditional and indigenous survival activities to new livelihood approach that is considered impious by the other community. This paper argues about the sustainability of livelihood strategies in terms of adaptation and transformation after the livelihood shocks. The resilient and sustainable livelihood perspective is used as a theoretical lens to discuss the livelihood circumstances of the Dom community of the study area. Furthermore, the resilience perspective enhanced the analysis of livelihood transformation in the present context in terms of the disaster the research participants have been surviving with.